2020
DOI: 10.3390/vetsci7040187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Genotyping of Infectious Bronchitis Virus and Avian Metapneumovirus in Backyard and Commercial Chickens in Jimma Zone, Southwestern Ethiopia

Abstract: Poultry production plays a relevant role in the Ethiopian economy and represents a source of poverty alleviation for several social classes. Infectious diseases can therefore significantly impact the economy and welfare. Despite infectious bronchitis virus (IBV) and avian metapneumovirus (aMPV) being present, the knowledge of their epidemiology and impact is extremely limited. In the present work, a cross-sectional study based on 500 tracheal swabs collected from 50 intensive and backyard unvaccinated flocks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…However, the prevalence obtained for Oyo state in this study (50%) was lower than 78.32% reported by Emikpe et al in 2010 in the same location. Generally, the prevalence among local chickens in this study (49.1%) was higher than 21.2% reported in Ghana (Ayim-Akonor et al, 2018) but lower than 74.9% reported in Ethiopia among unvaccinated backyard chickens (Tesfaye et al, 2019). This cross-country seroprevalence differences might have resulted from varying environmental factors (which could mitigate the spread of IBV among local chickens), availability and use of IBV vaccine and hygiene practise.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the prevalence obtained for Oyo state in this study (50%) was lower than 78.32% reported by Emikpe et al in 2010 in the same location. Generally, the prevalence among local chickens in this study (49.1%) was higher than 21.2% reported in Ghana (Ayim-Akonor et al, 2018) but lower than 74.9% reported in Ethiopia among unvaccinated backyard chickens (Tesfaye et al, 2019). This cross-country seroprevalence differences might have resulted from varying environmental factors (which could mitigate the spread of IBV among local chickens), availability and use of IBV vaccine and hygiene practise.…”
Section: Discussioncontrasting
confidence: 60%
“…Tesfaye et al [ 21 ] identified four serotypes of infectious bronchitis virus, namely, M41, D-274, 793B, and QX from unvaccinated backyard and commercial farms. Similarly, Tegegne et al [ 22 ] detected IBV 793B (GI-13) strains in backyard flocks in Jimma Zone, with a prevalence of 6%. Besides, Hutton et al [ 20 ] reported the detection of variant IBV (793B genotype) from the Ethiopian Institute of Agricultural Research (EIAR), located in Debre Zeit where no vaccination protocol has been implemented.…”
Section: Discussionmentioning
confidence: 98%
“…Tesfaye et al [ 21 ] also reported M41, D-274, 793B, and QX serotypes, with a prevalence of 74.88% and 68.75% in the unvaccinated backyard and commercial farms, respectively. Moreover, Tegegne et al [ 22 ] detected IBV 793B (GI-13) strains, with a prevalence of 6% from intensive and backyard unvaccinated flocks of the Jimma Zone. There was no study in northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the reported prevalence of aMPV was low (<30%) in many countries; for example, it was 1.04% in Ethiopia [42], 2.8% in Greece [43], 13.3% in Jordan [16] and 25.6% in Italy [44]. The detection rates of aMPV in northern Vietnam (17.2%) demonstrated a similar low prevalence to other countries.…”
Section: The Detection Rates Of Ampv Infectionsmentioning
confidence: 88%